ʼA rhaṅʻ Nāgasenābhivaṃsa (Dhammācariya) pru cu cī raṅʻ ʼapʻ so ʼA rhaṅʻ Nāgasinʻ Puṃ pra cheʺ ʼabhidhānʻ - Nāgasenābhivaṃsa, Mahātherʻ (Mranʻ mā praññʻ Cā ʼupʻ Tuikʻ, 1969)
Dictionary of medicinal plants in Burma.